The long and the short of it: the MDM4 tail so far. (28th March 2019) - Haupt, Sue; Mejía-Hernández, Javier Octavio; Vijayakumaran, Reshma; Keam, Simon P; Haupt, Ygal
Abstract: The mouse double minute 4 (MDM4) is emerging from the shadow of its more famous relative MDM2 and is starting to steal the limelight, largely due to its therapeutic possibilities. MDM4 is a vital regulator of the tumor suppressor p53. It restricts p53 transcriptional activity and also, at least in development, facilitates MDM2's E3 ligase activity toward p53. These functions of MDM4 are critical for normal cell function and a proper response to stress. Their importance for proper cell maintenance and proliferation identifies them as a risk for deregulation associated with the uncontrolled growth of cancer. MDM4 tails are vital for its function, where its N-terminus transactivation domain engages p53 and its C-terminus RING domain binds to MDM2. In this review, we highlight recently identified cellular functions of MDM4 and survey emerging therapies directed to correcting its dysregulation in disease.